Textured (1-z)CaTiO3-zLaAlO3 ceramic materials and their preparation methods, and communication devices

By using molten salt method and high-temperature solid state synthesis method in (1-z)CaTiO3-zLaAlO3 ceramic material to prepare the textured structure, the problem of low thermal conductivity of ceramic materials is solved, and high thermal conductivity and high dielectric constant are achieved. Combined, the performance of communication devices is improved.

CN116924792BActive Publication Date: 2024-12-13ANHUI TATFOOK TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310763137.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2024-12-13
Estimated Expiration
2043-06-25

AI Technical Summary

Technical Problem

The current (1-z)CaTiO3-zLaAlO3 ceramic materials have low thermal conductivity, resulting in limited heat dissipation of dielectric resonators in high-power dielectric cavity filters and inability to conduct heat in time.

Method used

Preparation of (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystals and high-temperature solid-state synthesis method (1-y)CaTiO3-yLaAlO3 ceramic powder. The ceramic green body has a textured structure and heat Rapid conduction in the preferred orientation and improve thermal conductivity.

Benefits of technology

Significantly improves the thermal conductivity of (1-z)CaTiO3-zLaAlO3 ceramic materials, reaching 20-40W/m·k, and maintains a high dielectric constant and resonant frequency temperature coefficient, which improves the reliability and signal of communication devices. Transmission efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116924792B_ABST
    Figure CN116924792B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of ceramic materials, and in particular, relates to a textured (1‑z)CaTiO3‑zLaAlO3 ceramic material and a preparation method thereof, as well as a communication device. The preparation method of the textured (1‑z)CaTiO3‑zLaAlO3 ceramic material comprises the steps of: preparing (1‑x)CaTiO3‑xLaAlO3 ceramic flaky template seed crystals by a molten salt method; preparing (1‑y)CaTiO3‑yLaAlO3 ceramic powder by a high-temperature solid-state synthesis method; mixing the ceramic flaky template seed crystals with the ceramic powder to form a ceramic green body, sintering the ceramic powder, and preferentially growing the ceramic powder in the flaky direction of the template seed crystal to obtain a textured ceramic material. Heat can be quickly conducted in these preferential orientations, thereby improving the thermal conductivity of the ceramic material, so that the textured ceramic material has the characteristics of high thermal conductivity, high dielectric constant, high quality factor, and near-zero resonant frequency temperature coefficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of ceramic materials, and in particular relates to a textured (1-z) CaTiO3-zLaAlO3 ceramic material and a preparation method thereof, as well as a communication device. Background Art

[0002] The dielectric resonator is one of the most important components in the dielectric cavity filter of the 5G macro base station. Compared with the metal cavity resonator, the dielectric resonator made of microwave dielectric ceramic material has the advantages of light weight, small size, good temperature coefficient stability, and low price. For high-power dielectric cavity filters, since the dielectric resonator usually has a small thermal conductivity value, the heat is easily concentrated in the dielectric resonator and cannot be conducted out in time, which poses a serious challenge to the heat dissipation of the filter. CaTiO3 has an orthorhombic perovskite structure, and its relative dielectric constant ε r =162, quality factor Q×F value = 1290GHz, resonant frequency temperature coefficient τ f =859ppm / ℃; LaAlO3 has a rhombohedral perovskite structure, and its relative dielectric constant ε r =23.4, quality factor Q×F value = 68000GHz, resonant frequency temperature coefficient τ f =-44ppm / ℃, ceramics based on (1-z)CaTiO3-zLaAlO3 (CTLA, 0<z<1) solid solution are expected to become microwave dielectric materials with excellent performance.

[0003] At present, (1-z)CaTiO3-zLaAlO3 (CTLA) ceramics are low-cost, high-performance, and large-scale microwave dielectric ceramic materials used in communication products such as dielectric resonators. The thermal conductivity of this ceramic material is low, about 3.7W / m·k, and its thermal conductivity is poor. How to further improve the thermal conductivity of (1-z)CaTiO3-zLaAlO3 ceramics has become one of the main challenges at present. Summary of the invention

[0004] The purpose of this application is to provide a textured (1-z)CaTiO3-zLaAlO3 ceramic material and a preparation method thereof, as well as a communication device, aiming to improve the thermal conductivity of (1-z)CaTiO3-zLaAlO3 ceramics to a certain extent.

[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0006] In a first aspect, the present application provides a method for preparing a textured (1-z) CaTiO3-zLaAlO3 ceramic material, comprising the following steps:

[0007] (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystals are prepared by a molten salt method, wherein 0<x<1;

[0008] (1-y)CaTiO3-yLaAlO3 ceramic powder is prepared by high temperature solid state synthesis method, wherein 0<y<1;

[0009] The (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal is mixed with the (1-y)CaTiO3-yLaAlO3 ceramic powder to form a ceramic green body, which is sintered to obtain a textured (1-z)CaTiO3-zLaAlO3 ceramic material, wherein 0<z<1.

[0010] In some possible implementations, the steps of preparing the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal include:

[0011] The flaky titanium source is prepared by molten salt method;

[0012] According to the stoichiometric ratio of the metal elements in (1-x)CaTiO3-xLaAlO3, the flaky titanium source, the first aluminum source, the first La source, the first calcium source and the first shape-adjusting molten salt are mixed to form a mixed material, and then subjected to a first calcination treatment to obtain a first calcined powder;

[0013] The first calcined powder is sequentially acid-washed and water-washed to remove impurities, thereby obtaining the (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal.

[0014] In some possible implementations, the flake titanium source includes Bi4Ti3O 12 , prepare the Bi4Ti3O 12 The steps of forming a flake titanium source include: 12 The stoichiometric ratio of the metal elements in the mixture is obtained by mixing bismuth trioxide and titanium dioxide into a mixed material, mixing the mixed material with a second shape-adjusting molten salt, performing a second calcination treatment, washing with water and drying, and obtaining the Bi4Ti3O 12 Flake titanium source.

[0015] In some possible implementations, the mass ratio of the total mass of the flaky titanium source, the first aluminum source, the first lanthanum source and the first calcium source to the mass of the first shape-adjusting molten salt is 1:(2-2.5).

[0016] In some possible implementations, the conditions of the first calcination treatment include: calcining at a temperature of 1050-1250° C. for 4-6 hours.

[0017] In some possible implementations, the solution used for pickling includes at least one of nitric acid and hydrochloric acid.

[0018] In some possible implementations, the first lanthanum source includes at least one of lanthanum oxide, lanthanum carbonate, and lanthanum hydroxide.

[0019] In some possible implementations, the first aluminum source includes at least one of aluminum oxide and aluminum hydroxide.

[0020] In some possible implementations, the first calcium source includes at least one of calcium carbonate and calcium hydroxide.

[0021] In some possible implementations, the first shape-adjusting molten salt and the second shape-adjusting molten salt respectively and independently include NaCl and KCl in a mass ratio of 1:(0.5-1.5).

[0022] In some possible implementations, the mass ratio of the total mass of the bismuth trioxide and the titanium dioxide to the mass of the second shape-adjusting molten salt is 1:(2-2.5).

[0023] In some possible implementations, the conditions of the second calcination treatment include: calcining at a temperature of 900 to 1100° C. for 4 to 6 hours.

[0024] In some possible implementations, the size of the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal is 10 to 100 μm.

[0025] In some possible implementations, the steps of preparing the (1-y)CaTiO3-yLaAlO3 ceramic powder include:

[0026] According to the stoichiometric ratio of the metal elements in (1-y)CaTiO3-yLaAlO3, a second aluminum source, a second La source, a second titanium source and a second calcium source are mixed to form a mixed material, and then subjected to a third calcination treatment to obtain a third calcined powder;

[0027] The third calcined powder is mixed with a binder and then spray granulated to obtain the (1-y)CaTiO3-yLaAlO3 ceramic powder.

[0028] In some possible implementations, the second lanthanum source includes at least one of lanthanum oxide, lanthanum carbonate, and lanthanum hydroxide.

[0029] In some possible implementations, the second aluminum source includes at least one of aluminum oxide and aluminum hydroxide.

[0030] In some possible implementations, the second titanium source includes at least one of titanium dioxide and titanium hydroxide.

[0031] In some possible implementations, the second calcium source includes at least one of calcium carbonate and calcium hydroxide.

[0032] In some possible implementations, the adhesive includes at least one of polyvinyl alcohol, hydroxypropyl methylcellulose, and polyacrylic acid.

[0033] In some possible implementations, the temperature conditions of the third calcination treatment include: calcining at a temperature of 1050-1250° C. for 4-6 hours.

[0034] In some possible implementations, the mass ratio of the third calcined powder to the binder is 1:(0.15-0.2).

[0035] In some possible implementations, the average particle size of the (1-y)CaTiO3-yLaAlO3 ceramic powder is 0.5 to 5 μm.

[0036] In some possible implementations, the mass ratio of the (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal to the (1-y)CaTiO3-yLaAlO3 ceramic powder is (0.02-0.05):1.

[0037] In some possible implementations, the preparation steps of the ceramic green body include: mixing the (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal with the (1-y)CaTiO3-yLaAlO3 ceramic powder, transferring the mixed powder into a mold, and pressing it into the ceramic green body under a pressure of 150 to 250 MPa.

[0038] In some possible implementations, the sintering treatment conditions are: sintering at a temperature of 1430-1470° C. for 4-6 hours.

[0039] In the second aspect, the present application provides a textured (1-z)CaTiO3-zLaAlO3 ceramic material prepared by the above method, wherein the textured (1-z)CaTiO3-zLaAlO3 ceramic material includes a (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal and a (1-y)CaTiO3-yLaAlO3 ceramic powder grown along the (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal.

[0040] In some possible implementations, the thermal conductivity of the textured (1-z) CaTiO3-zLaAlO3 ceramic material is 20 to 40 W / m·k.

[0041] In a third aspect, the present application provides a communication device, wherein the raw materials for manufacturing the communication device include a method for preparing a textured (1-z) CaTiO3-zLaAlO3 ceramic material prepared as described above, or a method for preparing the textured (1-z) CaTiO3-zLaAlO3 ceramic material described above.

[0042] The first aspect of the present application provides a method for preparing a textured (1-z)CaTiO3-zLaAlO3 ceramic material, which comprises preparing (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystals by a molten salt method; and preparing (1-y)CaTiO3-yLaAlO3 ceramic powder by a high-temperature solid-state synthesis method, mixing the (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystals with the (1-y)CaTiO3-yLaAlO3 ceramic powder to form a ceramic green body, and then performing a sintering treatment. During the sintering process, with the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal as the crystal nucleus, the (1-y)CaTiO3-yLaAlO3 ceramic powder grains are regularly arranged along the flake direction of the template seed crystal, and orientation-preferred growth is carried out in the flake direction of the template seed crystal, thereby realizing the material structure design and tailoring at the grain scale, so that the obtained (1-z)CaTiO3-zLaAlO3 ceramic material has a textured structure. In the textured (1-z)CaTiO3-zLaAlO3 ceramic material, heat can be quickly conducted in the textured preferred orientation, thereby significantly improving the thermal conductivity of the textured (1-z)CaTiO3-zLaAlO3 ceramic material. The obtained textured (1-z)CaTiO3-zLaAlO3 ceramic material has the characteristics of high thermal conductivity, high dielectric constant, high quality factor and near-zero resonant frequency temperature coefficient.

[0043] The textured (1-z) CaTiO3-zLaAlO3 ceramic material provided in the second aspect of the present application is prepared by the above method, including (1-x) CaTiO3-xLaAlO3 ceramic flake template seed crystals and (1-y) CaTiO3-yLaAlO3 ceramic powders grown along the (1-x) CaTiO3-xLaAlO3 ceramic flake template seed crystals, and orientation-preferred growth is carried out in the flake direction of the template seed crystals to obtain the textured (1-z) CaTiO3-zLaAlO3 ceramic material. Heat can be quickly conducted in these preferred orientations, which can significantly improve the thermal conductivity of the textured (1-z) CaTiO3-zLaAlO3 ceramic material, so that the textured (1-z) CaTiO3-zLaAlO3 ceramic material has the characteristics of high thermal conductivity, high dielectric constant, high quality factor and near-zero resonant frequency temperature coefficient.

[0044] The communication device provided in the third aspect of the present application is beneficial to improving the reliability, stability and signal transmission efficiency of the communication device because the raw materials used to manufacture the communication device include the above-mentioned textured (1-z) CaTiO3-zLaAlO3 ceramic material with properties such as high thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0046] Figure 1 1 is a schematic flow chart of a method for preparing a textured (1-z) CaTiO3-zLaAlO3 ceramic material provided in an embodiment of the present application;

[0047] Figure 2 It is a schematic diagram of a process for preparing a textured (1-z) CaTiO3-zLaAlO3 ceramic material provided in an embodiment of the present application;

[0048] Figure 3 It is a schematic flow chart of the method for preparing the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal provided in Example 1 of the present application;

[0049] Figure 4 It is a schematic flow chart of the method for preparing the (1-y)CaTiO3-yLaAlO3 ceramic powder provided in Example 1 of the present application. DETAILED DESCRIPTION

[0050] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0051] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0052] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0053] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0054] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0055] The weight of the relevant components mentioned in the embodiments of the present specification can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present specification is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present specification. Specifically, the mass described in the embodiments of the present specification can be μg, mg, g, kg and other mass units known in the chemical industry.

[0056] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0057] Anisotropy is the most basic intrinsic property of crystalline materials, and anisotropy also appears in the preparation process of various polycrystalline materials. During the preparation process of solidification, deformation, recrystallization, solid-state phase change, sintering and heat treatment of materials, materials often generate specific anisotropy under external physical conditions such as anisotropic force field, electric field, magnetic field, temperature gradient field, as well as chemical driving force, grain boundary energy, phase boundary energy, surface energy, and other intrinsic factors of material organization structure, and evolve according to specific laws. The basic law of material processing under anisotropic external field determines that anisotropic crystals will form non-random polycrystalline orientation distribution forms in different forms, that is, various types of textures.

[0058] The textured (1-z)CaTiO3-zLaAlO3 ceramic material of the present application, wherein 0<z<1, refers to the use of certain microstructure control means to make the anisotropic grains in the microstructure of the structural ceramic material to be regularly arranged along certain specific directions, or to increase the probability of orientation in these directions, so that it grows preferentially. The following embodiments are used as examples for exemplary explanation.

[0059] As attached Figure 1 and 2 As shown, the first aspect of the embodiment of the present application provides a method for preparing a textured (1-z) CaTiO3-zLaAlO3 ceramic material, comprising the following steps:

[0060] S10. Prepare (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystals by molten salt method, wherein 0<x<1;

[0061] S20. Prepare (1-y)CaTiO3-yLaAlO3 ceramic powder by high temperature solid state synthesis method, wherein 0<y<1;

[0062] S30. Mix the (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal with the (1-y)CaTiO3-yLaAlO3 ceramic powder to form a ceramic green body, and then sinter it to obtain a textured (1-z)CaTiO3-zLaAlO3 ceramic material, wherein 0<z<1.

[0063] The first aspect of the embodiment of the present application provides a method for preparing a textured (1-z)CaTiO3-zLaAlO3 ceramic material, which comprises preparing (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystals by a molten salt method; and preparing (1-y)CaTiO3-yLaAlO3 ceramic powder by a high-temperature solid-state synthesis method, and then mixing the (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystals with the (1-y)CaTiO3-yLaAlO3 ceramic powder to form a ceramic green body, which is then sintered. During the sintering process, the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal is used as the crystal nucleus, and the (1-y)CaTiO3-yLaAlO3 ceramic powder grains are regularly arranged along the flake direction of the template seed crystal, and orientation-preferred growth is carried out in the flake direction of the template seed crystal, thereby realizing material structure design and tailoring at the grain scale, so that the obtained (1-z)CaTiO3-zLaAlO3 ceramic material has a textured structure. In the textured (1-z)CaTiO3-zLaAlO3 ceramic material, heat can be quickly conducted in the textured preferred orientation, thereby significantly improving the thermal conductivity of the textured (1-z)CaTiO3-zLaAlO3 ceramic material. The obtained textured (1-z)CaTiO3-zLaAlO3 ceramic material has the characteristics of high thermal conductivity, high dielectric constant, high quality factor and near-zero resonant frequency temperature coefficient.

[0064] In some possible implementations, in the textured (1-z) CaTiO3-zLaAlO3 ceramic material, 0<z<1. Further, 0.2<z<0.5. Exemplarily, the textured (1-z) CaTiO3-zLaAlO3 ceramic material may be 0.7CaTiO3-0.3LaAlO3 ceramic material, etc.

[0065] In some possible implementations, in the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal, 0<x<1. Further, 0.2<x<0.5. Exemplarily, the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal can be a 0.7CaTiO3-0.3LaAlO3 ceramic flake template seed crystal, etc.

[0066] In some possible implementations, in the (1-y)CaTiO3-yLaAlO3 ceramic powder, 0<y<1. Further, 0.2<y<0.5. Exemplarily, the (1-y)CaTiO3-yLaAlO3 ceramic powder may be 0.7CaTiO3-0.3LaAlO3 ceramic powder, etc.

[0067] In some embodiments, x in the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal and y in the (1-y)CaTiO3-yLaAlO3 ceramic powder have the same value. In this case, z=x=y in the obtained textured (1-z)CaTiO3-zLaAlO3 ceramic material.

[0068] In some embodiments, the values ​​of x in the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal and y in the (1-y)CaTiO3-yLaAlO3 ceramic powder are different. In this case, the value of z in the obtained textured (1-z)CaTiO3-zLaAlO3 ceramic material varies with the sizes of x and y, as well as the ratio of the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal and the (1-y)CaTiO3-yLaAlO3 ceramic powder.

[0069] In some possible implementations, the thermal conductivity of the textured (1-z)CaTiO3-zLaAlO3 ceramic material is 20 to 40 W / m·k, which has good thermal conductivity. The heat in the device can be conducted away in time, giving it better application prospects in fields such as high-power dielectric filters.

[0070] In some possible implementations, in the above step S10, the step of preparing (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystals includes:

[0071] S11. Prepare a flaky titanium source by a molten salt method. The present embodiment adopts a molten salt method to prepare a flaky titanium source, wherein the raw material for preparing the titanium source is dissolved in a molten salt with a low melting point at high temperature to form a saturated solution, and then the molten solution is placed in a supersaturated state by slowly cooling the temperature or evaporating the flux at a constant temperature, so that the titanium source crystals precipitate and grow in a specific flaky structure to obtain a flaky titanium source.

[0072] S12. According to the stoichiometric ratio of the metal elements in (1-x)CaTiO3-xLaAlO3, the flaky titanium source, the first aluminum source, the first lava source, the first calcium source and the first shape-adjusting molten salt are mixed to form a mixed material, and then the mixed material is subjected to a first calcination treatment to obtain a first calcined powder. During the calcination process, the raw material components can fully undergo a self-contained chemical reaction under the action of the first shape-adjusting molten salt, so that (1-x)CaTiO3-xLaAlO3 is precipitated and grown in a specific flaky structure.

[0073] S13. The first calcined powder is sequentially acid-washed and water-washed to remove impurities, and unreacted raw material components, residual first shape adjustment molten salt, and generated by-products and other impurities are fully removed to obtain (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystals.

[0074] In some possible implementations, in the above step S11, the flake titanium source includes Bi4Ti3O 12 , preparation of Bi4Ti3O 12 The steps of forming a flake titanium source include: 12 The stoichiometric ratio of the metal elements in the mixture is obtained by mixing bismuth trioxide and titanium dioxide, and then mixing the mixture with the second shape-adjusting molten salt, performing a second calcination treatment, washing with water, and drying to obtain Bi4Ti3O 12 During the calcination process of the embodiment of the present application, the second shape-adjusting molten salt can adjust the shape of the precipitated titanium source to obtain Bi4Ti3O 12 The flaky titanium source is calcined and the product is washed with water to remove the residual second shape adjustment molten salt, as well as residual unreacted raw materials, by-products and other impurities.

[0075] In some possible implementations, the second shape-adjusting molten salt includes NaCl and KCl in a mass ratio of 1:(0.5-1.5); specifically, the mass ratio of NaCl and KCl can be 1:(0.5-0.8), 1:(0.8-1.0), 1:(1.0-1.2), 1:(1.2-1.5), etc. In this case, the molten salt can well adjust the Bi4Ti3O 12 The shape of the titanium source is to obtain a flake-shaped titanium source.

[0076] In some possible implementations, the mass ratio of the total mass of bismuth trioxide and titanium dioxide to the mass ratio of the second shape-adjusting molten salt is 1:(2-2.5); for example, the mass ratio may be 1:(2-2.2), 1:(2.2-2.4), 1:(2.4-2.5), etc. Under this mass ratio, the shape of the titanium source can be well adjusted to obtain Bi4Ti3O 12 Flake titanium source.

[0077] In some possible implementations, the conditions of the second calcination treatment include: calcining at a temperature of 900-1100°C for 4-6 hours. Under this condition, the bismuth trioxide and titanium dioxide raw material components can fully undergo a self-contained chemical reaction under the action of the second shape-adjusting molten salt, and the chemical reaction equation is: 2Bi2O3+3TiO2=Bi4Ti3O 12 , obtain Bi4Ti3O 12 Flake titanium source.

[0078] In some specific embodiments, Bi4Ti3O 12 The steps of forming a flake titanium source include: 12The raw materials are fed in a molar ratio, wherein the purity of bismuth trioxide (Bi2O3), titanium dioxide (TiO2), sodium chloride (NaCl) and potassium chloride (KCl) are all above 99%. The raw materials are placed in an oven at 100-150°C for 10-20 hours for standby use. A certain proportion of the raw materials are accurately weighed using an electronic balance. The weighed raw materials are transferred to a polyurethane ball mill for wet grinding, wherein the mass ratio of material: ball: deionized water is 1: (3-4): (1.6-2.2), and the ball mill speed is 250-350r / min. After ball milling for 4-6 hours, the slurry is transferred to an oven at 100-150°C for drying, and then crushed and sieved to obtain a mixed material (first mixed powder). The mixed material (first mixed powder) is evenly mixed with a second shape-adjusting molten salt (exemplarily NaCl and KCl with a molar ratio of 1: (0.5-1.5)) of 2-2.5 times its mass to obtain a second mixed powder. The second mixed powder was transferred to a sealed alumina crucible and calcined in a high temperature furnace at 900-1100°C for 4-6 hours to obtain a second calcined powder. The second calcined powder was repeatedly rinsed with hot deionized water to remove residual NaCl and KCl salts, residual unreacted bismuth trioxide, titanium dioxide raw materials, by-products and other impurities. The rinsed powder was transferred to an oven at 100-150°C for drying, and then crushed and sieved to obtain Bi4Ti3O 12 Flake titanium source.

[0079] In some possible implementations, in the above step S12, the mass ratio of the total mass of the flaky titanium source, the first aluminum source, the first La source and the first calcium source to the first shape-adjusting molten salt is 1:(2-2.5); illustratively, the mass ratio may be 1:(2-2.2), 1:(2.2-2.4), 1:(2.4-2.5), etc. Under this mass ratio, the shape of the titanium source can be well adjusted to obtain a (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal.

[0080] In some possible implementations, the first shape-adjusting molten salt includes NaCl and KCl in a mass ratio of 1:(0.5-1.5); specifically, the mass ratio of NaCl and KCl can be 1:(0.5-0.8), 1:(0.8-1.0), 1:(1.0-1.2), 1:(1.2-1.5), etc. In this case, the molten salt can well adjust the shape of (1-x)CaTiO3-xLaAlO3 to obtain (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystals.

[0081] In some possible implementations, the conditions of the first calcination treatment include: calcining at a temperature of 1050-1250° C. for 4-6 hours; under this condition, the raw material components such as the flaky titanium source, the first aluminum source, the first aluminum source and the first calcium source can fully undergo a self-assembly chemical reaction under the action of the first shape-adjusting molten salt, and the chemical reaction equation is: 2(1-x)Bi4Ti3O 12 +6(1-x)CaCO3+3xLa2O3+3xAl2O3=6(1-x)CaTiO3-xLaAlO3+4(1-x)Bi2O3+6(1-x)CO2, to obtain (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal.

[0082] In some possible implementations, the first lanthanum source includes at least one of lanthanum oxide, lanthanum carbonate, and lanthanum hydroxide.

[0083] In some possible implementations, the first aluminum source includes at least one of aluminum oxide and aluminum hydroxide.

[0084] In some possible implementations, the first calcium source includes at least one of calcium carbonate and calcium hydroxide.

[0085] In some possible implementations, in the above step S13, the pickling solution includes at least one of nitric acid and hydrochloric acid. Exemplarily, 30% nitric acid is used for soaking for 12 to 24 hours to fully remove impurities such as by-products and unreacted raw materials.

[0086] In some specific embodiments, the steps of preparing (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystals include: using calcium carbonate (CaCO3), lanthanum oxide (La2O3) and aluminum oxide (Al2O3) as the first calcium source, the first lanthanum source and the first aluminum source respectively, wherein the first calcium source can also be calcium hydroxide, and the first lanthanum source can also be lanthanum carbonate or lanthanum hydroxide. The purity of calcium carbonate, lanthanum oxide and aluminum oxide are all above 99%. 12 The flake titanium source and CaCO3, La2O3, Al2O3 powders are reacted according to the chemical reaction equation 2(1-x)Bi4Ti3O 12+6(1-x)CaCO3+3xLa2O3+3xAl2O3=6(1-x)CaTiO3-xLaAlO3+4(1-x)Bi2O3+6(1-x)CO2 in a stoichiometric ratio. Furthermore, to ensure sufficient reaction, the ratio of the molar amount of the titanium source to the total molar amount of the calcium source, the La source and the aluminum source satisfies 1:10. When the calcium source, the La source and the aluminum source are slightly excessive, it is more conducive to improving the preparation yield of the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal. At the same time, a first shape-adjusting molten salt (exemplarily NaCl and KCl with a molar ratio of 1:(0.5-1.5)) with a mass of 2 to 2.5 times the mass of the mixed powder is added to prepare a mixed material. The mixed material is transferred to a sealed alumina crucible and calcined in a high-temperature furnace at 900-1100°C for 4-6 hours to obtain a first calcined powder. The first calcined powder is repeatedly soaked in 30% nitric acid (HNO3) for 12 to 24 hours to remove bismuth-based byproducts, unreacted CaCO3, La2O3, Al2O3 powders, and CaO, a decomposition product of CaCO3. The acid-washed powder is repeatedly rinsed with hot deionized water, and then dried, crushed, and sieved to obtain a composite perovskite (1-x)CaTiO3-xLaAlO3 (CTLA) ceramic flake template seed crystal.

[0087] In some possible implementations, the size of the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal is 10-100 μm. In some specific embodiments, the size of the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal can be 10-20 μm, 20-30 μm, 30-40 μm, 40-50 μm, 50-60 μm, 60-70 μm, 70-80 μm, 80-90 μm, 90-100 μm, etc.

[0088] In some possible implementations, in the above step S20, the step of preparing (1-y)CaTiO3-yLaAlO3 ceramic powder includes:

[0089] S21. According to the stoichiometric ratio of the metal elements in (1-y)CaTiO3-yLaAlO3, a second aluminum source, a second Lan source, a second titanium source and a second calcium source are mixed to form a mixture, and then subjected to a third calcination treatment. During the calcination process, the raw material components are self-assembled into (1-y)CaTiO3-yLaAlO3 grains, which are ground to obtain a third calcined powder;

[0090] S22. After mixing the third calcined powder with a binder, spray granulation is performed to obtain (1-y)CaTiO3-yLaAlO3 ceramic powder. The added binder is used to improve the bonding performance between powder particles, which is beneficial to the subsequent powder shaping, and a small-particle-size (1-y)CaTiO3-yLaAlO3 ceramic powder is obtained by spray granulation.

[0091] In some possible implementations, in the above step S21, the temperature conditions of the third calcination treatment include: calcining at a temperature of 1050-1250°C for 4-6 hours; under this condition, the raw material components such as the second magnesium source, the second titanium source and the second calcium source can fully undergo self-chemical reaction to form (1-y)CaTiO3-yLaAlO3 grains.

[0092] In some possible implementations, the second lanthanum source includes at least one of lanthanum oxide, lanthanum carbonate, and lanthanum hydroxide.

[0093] In some possible implementations, the second aluminum source includes at least one of aluminum oxide and aluminum hydroxide.

[0094] In some possible implementations, the second titanium source includes at least one of titanium dioxide and titanium hydroxide.

[0095] In some possible implementations, the second calcium source includes at least one of calcium carbonate and calcium hydroxide.

[0096] In some possible implementations, in the above step S22, the adhesive includes at least one of polyvinyl alcohol, hydroxypropyl methylcellulose, and polyacrylic acid; these adhesives can improve the bonding performance between powder particles, which is beneficial for subsequent powder shaping.

[0097] In some possible implementations, the mass ratio of the third calcined powder to the binder is 1:(0.15-0.2); specifically, the mass ratio may be 1:(0.15-0.16), 1:(0.16-0.18), 1:(0.18-0.20), etc. In this case, the amount of binder added ensures the bonding and molding performance between the powders while avoiding adding too much to affect the physical and chemical properties of the ceramic material.

[0098] In some possible implementations, the average particle size of the (1-y)CaTiO3-yLaAlO3 ceramic powder is 0.5 to 5 μm. Under this particle size condition, the powder particle size is small and the uniformity is high, which is more conducive to the subsequent full mixing of ceramic materials, and facilitates the subsequent sintering process. The (1-y)CaTiO3-yLaAlO3 ceramic powder is oriented along the specific direction of the (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal to form a stable textured (1-z)CaTiO3-zLaAlO3 ceramic material. Exemplarily, the average particle size of the (1-y)CaTiO3-yLaAlO3 ceramic powder can be 0.5 to 1 μm, 1 to 2 μm, 2 to 3 μm, 3 to 4 μm, 4 to 5 μm, etc.

[0099] In some specific embodiments, the steps of preparing (1-y)CaTiO3-yLaAlO3 ceramic powder include: using calcium carbonate (CaCO3), titanium dioxide (TiO2), lanthanum oxide (La2O3) and aluminum oxide (Al2O3) as starting materials, wherein the second calcium source can also be selected from calcium hydroxide, and the second lanthanum source can also be selected from lanthanum carbonate or lanthanum hydroxide. Feeding materials according to the molar ratio of the chemical formula (1-y)CaTiO3-yLaAlO3, wherein the purity of calcium carbonate, titanium dioxide, lanthanum oxide and aluminum oxide is above 99%. The raw materials are placed in an oven at 100-150°C and dried for 10-20 hours for standby use. An electronic balance is used to accurately weigh a certain proportion of the raw materials. The weighed raw materials are transferred to a polyurethane ball mill for a wet grinding, wherein the mass ratio of material: ball: deionized water = 1: (3-4): (1.6-2.2), and the ball mill speed is 250-350r / min. After ball milling for 4 to 6 hours, the slurry is transferred to a 100-150°C oven for drying, and then crushed and sieved to obtain a mixed material. The mixed material is calcined in a high-temperature furnace at 1050-1250°C for 4 to 6 hours to obtain a third calcined powder. The third calcined powder is transferred to a polyurethane ball mill for secondary wet grinding, wherein the mass ratio of material: ball: deionized water is 1: (3-4): (1-1.2), and the ball mill speed is 250-350r / min. After ball milling for 4 to 6 hours, an appropriate amount of adhesive (PVA, 15-20wt%) is added to the slurry, and then evenly stirred for 1 to 2 hours and spray granulated to obtain (1-y)CaTiO3-yLaAlO3 ceramic powder.

[0100] In some possible implementations, in the above step S30, the mass ratio of (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal to (1-y)CaTiO3-yLaAlO3 ceramic powder is (0.02-0.05): 1. In this case, the (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal and the (1-y)CaTiO3-yLaAlO3 ceramic powder are mixed to form a ceramic green body, and a small amount of (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal is added as a crystal nucleus. During the sintering process, the (1-y)CaTiO3-yLaAlO3 ceramic powder grains are regularly arranged along the flaky direction of the template seed crystal, and orientation-preferred growth is carried out in the flaky direction of the template seed crystal, thereby realizing material structure design and tailoring at the grain scale, so that the obtained (1-z)CaTiO3-zLaAlO3 ceramic material has a textured structure.

[0101] In some specific embodiments, the mass ratio of (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystal to (1-y)CaTiO3-yLaAlO3 ceramic powder can be (0.02~0.03):1, (0.03~0.04):1, (0.04~0.05):1, etc.

[0102] In some possible implementations, the steps of preparing the ceramic green body include: mixing (1-x)CaTiO3-xLaAlO3 ceramic flake template seed crystals with (1-y)CaTiO3-yLaAlO3 ceramic powder, transferring the mixed powder into a mold, and pressing the mixed powder into a ceramic green body at a pressure of 150 to 250 MPa. Specifically, the mixed raw materials may be transferred into a mold of a specific shape, and pressed on a dry pressing machine at a pressure of 150 to 250 MPa to obtain a green body block.

[0103] In some possible implementations, the sintering treatment conditions are: sintering at a temperature of 1430-1470°C for 4-6 hours. Under this temperature condition, the (1-y)CaTiO3-yLaAlO3 ceramic powder grains can be regularly arranged along the sheet direction of the (1-x)CaTiO3-xLaAlO3 ceramic sheet template seed crystal, and orientation-preferred growth can be carried out in the sheet direction of the template seed crystal, so that the (1-z)CaTiO3-zLaAlO3 ceramic material has a textured structure.

[0104] In some specific embodiments, the step of preparing a textured (1-z)CaTiO3-zLaAlO3 ceramic material includes: mixing (1-x)CaTiO3-xLaAlO3 flake template seed crystals and (1-y)CaTiO3-yLaAlO3 ceramic powder in a certain proportion, wherein the addition ratio of the (1-x)CaTiO3-xLaAlO3 flake template seed crystals is 2 to 5 wt%. Specifically, an electronic balance is used to accurately weigh a certain proportion of (1-x)CaTiO3-xLaAlO3 flake template seed crystals and (1-y)CaTiO3-yLaAlO3 ceramic powder, and the weighed raw materials are transferred to a V-type mixer for mixing, and the mixing time is 1 to 2 hours. The mixed raw materials are transferred to a mold of a specific shape, and pressed on a dry pressing machine at a pressure of 150 to 250 MPa to obtain a green block. The green block is sintered in a high temperature furnace at 1430-1470°C for 4-6 hours to obtain a textured (1-z)CaTiO3-zLaAlO3 ceramic material.

[0105] In the second aspect, an embodiment of the present application provides a textured (1-z)CaTiO3-zLaAlO3 ceramic material prepared by the above method, wherein the textured (1-z)CaTiO3-zLaAlO3 ceramic material includes a (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal and a (1-y)CaTiO3-yLaAlO3 ceramic powder grown along the (1-x)CaTiO3-xLaAlO3 ceramic flaky template seed crystal.

[0106] The textured (1-z) CaTiO3-zLaAlO3 ceramic material provided in the second aspect of the embodiment of the present application is prepared by the above method, including (1-x) CaTiO3-xLaAlO3 ceramic flake template seed crystals and (1-y) CaTiO3-yLaAlO3 ceramic powder grown along the (1-x) CaTiO3-xLaAlO3 ceramic flake template seed crystals, and orientation-preferred growth is carried out in the flake direction of the template seed crystals to obtain the textured (1-z) CaTiO3-zLaAlO3 ceramic material. Heat can be quickly conducted in these preferred orientations, which can significantly improve the thermal conductivity of the textured (1-z) CaTiO3-zLaAlO3 ceramic material, so that the textured (1-z) CaTiO3-zLaAlO3 ceramic material has the characteristics of high thermal conductivity, high dielectric constant, high quality factor and near-zero resonant frequency temperature coefficient.

[0107] In some possible implementations, the thermal conductivity of the textured (1-z)CaTiO3-zLaAlO3 ceramic material is 20 to 40 W / m·k, and its thermal conductivity is good, which makes it have better application prospects in the fields of dielectric filters, active antenna units, etc.

[0108] In a third aspect, an embodiment of the present application provides a communication device, wherein the raw materials for manufacturing the communication device include the preparation method of the textured (1-z) CaTiO3-zLaAlO3 ceramic material prepared by the above method, or the preparation method of the above-mentioned textured (1-z) CaTiO3-zLaAlO3 ceramic material.

[0109] The communication device provided in the third aspect of the embodiment of the present application is beneficial to improving the reliability, stability and signal transmission efficiency of the communication device because the raw materials used to manufacture the communication device include the above-mentioned textured (1-z)CaTiO3-zLaAlO3 ceramic material with properties such as high thermal conductivity.

[0110] In some possible implementations, communication devices include but are not limited to high-frequency communication devices such as high-power dielectric filters and dielectric resonators. Textured (1-z)CaTiO3-zLaAlO3 ceramic materials have good thermal conductivity, and the heat in the device can be conducted out in time, making it have better application prospects in the fields of high-power dielectric cavity filters.

[0111] In order to enable the above-mentioned implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to significantly demonstrate the improved performance of the textured (1-z) CaTiO3-zLaAlO3 ceramic material and its preparation method in the embodiment of the present application, the above-mentioned technical scheme is illustrated by means of multiple embodiments below.

[0112] Example 1

[0113] A textured 0.7CaTiO3-0.3LaAlO3 ceramic material, the preparation of which comprises the following steps:

[0114] ①Use bismuth trioxide, titanium dioxide, sodium chloride and potassium chloride with a purity of more than 99% as the starting materials. Place the raw materials in an oven at 120℃ and bake for 12 hours. 12 The stoichiometric ratio of the metal elements in the raw materials was added, and the weighed raw materials were transferred to a polyurethane ball mill for wet grinding, wherein the mass ratio of material: ball: deionized water = 1:3:1.6, and the ball mill speed was 300r / min. After ball milling for 4h, the slurry was transferred to a 120℃ oven for drying, and then crushed and sieved to obtain a mixed material (the first mixed powder). The first mixed powder was mixed evenly with 2.5 times the mass of the second shape-adjusting molten salt (the molar ratio of NaCl and KCl was 1:1) to obtain a second mixed powder. The second mixed powder was transferred to a sealed alumina crucible and calcined in a high-temperature furnace at 1000℃ for 6h to obtain a second calcined powder. The second calcined powder was repeatedly rinsed with hot deionized water to remove residual NaCl and KCl salts. The rinsed powder was transferred to a 120℃ oven for drying, and then crushed and sieved to obtain Bi4Ti3O 12Flake titanium source. Figure 3 shown.

[0115] ②Use calcium carbonate, lanthanum oxide and aluminum oxide with purity above 99% as starting materials. 12 The flake titanium source and CaCO3, La2O3, Al2O3 powders are reacted according to the chemical reaction equation 2(1-x)Bi4Ti3O 12 +6(1-x)CaCO3+3xLa2O3+3xAl2O3=6(1-x)CaTiO3-xLaAlO3+4(1-x)Bi2O3+6(1-x)CO2 in a stoichiometric ratio, wherein x=0.3, and the ratio of the molar amount of the titanium source to the total molar amount of the calcium source, the latitude source and the aluminum source satisfies 1:10 to ensure sufficient reaction, and at the same time, a first shape-adjusting molten salt (the molar ratio of NaCl and KCl is 1:1) with a mass of 2 times the mass of the mixed powder is added to prepare a mixed material. The mixed material is transferred to a sealed alumina crucible and calcined in a high-temperature furnace at 1000℃ for 4 hours to obtain a first calcined powder. The first calcined powder is repeatedly soaked in 30% nitric acid for 12 hours to remove bismuth-based byproducts, unreacted CaCO3, La2O3, Al2O3 powders, and CaO, a decomposition product of CaCO3. The acid-washed powder was repeatedly rinsed with hot deionized water, and then dried, crushed, and sieved to obtain composite perovskite 0.7CaTiO3-0.3LaAlO3 (CTLA) ceramic flake template seed crystals. Figure 3 shown.

[0116] ③ Use calcium carbonate (CaCO3), titanium dioxide (TiO2), lanthanum oxide (La2O3) and aluminum oxide (Al2O3) with a purity of more than 99% as starting materials. Place the raw materials in a 120℃ oven for 12 hours for standby use. Add materials according to the stoichiometric ratio of the metal elements in the chemical formula 0.7CaTiO3-0.3LaAlO3, transfer the weighed raw materials to a polyurethane ball mill for primary wet grinding, wherein the mass ratio of material: ball: deionized water is 1:3:1.6, and the ball mill speed is 300r / min. After ball milling for 4 hours, transfer the slurry to a 120℃ oven for drying, and then crush and sieve to obtain a mixed material. Calcine the mixed material in a high-temperature furnace at 1150℃ for 4 hours to obtain a third calcined powder. Transfer the third calcined powder to a polyurethane ball mill for secondary wet grinding, wherein the mass ratio of material: ball: deionized water is 1:3:1, and the ball mill speed is 300r / min. After ball milling for 4 hours, 17 wt% of the binder polyvinyl alcohol (PVA) was added to the slurry, and then stirred evenly for 1 hour and spray granulated to obtain 0.7CaTiO3-0.3LaAlO3 (CTLA) ceramic powder. Figure 4 shown.

[0117] ④ Use an electronic balance to accurately weigh a certain proportion of 0.7CaTiO3-0.3LaAlO3 (CTLA) ceramic flake template seed crystals and 0.7CaTiO3-0.3LaAlO3 (CTLA) ceramic powder material, wherein the addition ratio of 0.7CaTiO3-0.3LaAlO3 (CTLA) ceramic flake template seed crystals is 3.5wt%. Transfer the weighed raw materials to a V-type mixer for mixing, and the mixing time is 1.5h. Transfer the mixed raw materials to a mold with a diameter of Φ12mm, and press them on a dry pressing machine with a pressure of 200MPa to obtain a green block. Sinter the green block in a high-temperature furnace at 1450℃ for 4h to obtain a textured 0.7CaTiO3-0.3LaAlO3 ceramic material. As shown in the attached Figure 2 shown.

[0118] Example 2

[0119] A textured 0.7CaTiO3-0.3LaAlO3 ceramic material, the preparation of which comprises the following steps:

[0120] Steps ① to ③ are the same as steps ① to ③ in Example 1;

[0121] ④ Accurately weigh a certain proportion of 0.7CaTiO3-0.3LaAlO3 ceramic template seed crystals and 0.7CaTiO3-0.3LaAlO3 powder material using an electronic balance, wherein the addition ratio of 0.7CaTiO3-0.3LaAlO3 flake template seed crystals is 2wt%. Transfer the weighed raw materials to a V-type mixer for mixing, and the mixing time is 1.5h. Transfer the mixed raw materials to a mold with a diameter of Φ12mm, and press them on a dry pressing machine with a pressure of 200MPa to obtain a green block. Sinter the green block in a high-temperature furnace at 1450℃ for 4h to obtain a textured 0.7CaTiO3-0.3LaAlO3 ceramic material.

[0122] Example 3

[0123] A textured 0.7CaTiO3-0.3LaAlO3 ceramic material, the preparation of which comprises the following steps:

[0124] Steps ① to ③ are the same as steps ① to ③ in Example 1;

[0125] ④ Accurately weigh a certain proportion of 0.7CaTiO3-0.3LaAlO3 ceramic flake template seed crystals and 0.7CaTiO3-0.3LaAlO3 powder material using an electronic balance, wherein the addition ratio of 0.7CaTiO3-0.3LaAlO3 flake template seed crystals is 5wt%. Transfer the weighed raw materials to a V-type mixer for mixing, and the mixing time is 1.5h. Transfer the mixed raw materials to a mold with a diameter of Φ12mm, and press them on a dry pressing machine with a pressure of 200MPa to obtain a green block. Sinter the green block in a high-temperature furnace at 1450℃ for 4h to obtain a textured 0.7CaTiO3-0.3LaAlO3 ceramic material.

[0126] Comparative Example 1 (using only sheet template seed crystal)

[0127] A 0.7CaTiO3-0.3LaAlO3 ceramic material, the preparation of which comprises the following steps:

[0128] ①Use bismuth trioxide, titanium dioxide, sodium chloride and potassium chloride with a purity of more than 99% as the starting materials. Place the raw materials in an oven at 120℃ and bake for 12 hours. 12 The raw materials were added in a molar ratio, and the weighed raw materials were transferred to a polyurethane ball mill for wet grinding, wherein the mass ratio of material: ball: deionized water was 1:3:1.6, and the ball mill speed was 300r / min. After ball milling for 4h, the slurry was transferred to a 120℃ oven for drying, and then crushed and sieved to obtain the first mixed powder. The first mixed powder was mixed evenly with 2.5 times the mass of salt (the molar ratio of NaCl and KCl was 1:1) to obtain a second mixed powder. The second mixed powder was transferred to a sealed alumina crucible and calcined in a high-temperature furnace at 1000℃ for 6h to obtain a calcined powder. The calcined powder was repeatedly rinsed with hot deionized water to remove residual NaCl and KCl salts. The rinsed powder was transferred to a 120℃ oven for drying, and then crushed and sieved to obtain Bi4Ti3O 12 Flaky powder.

[0129] ②Use calcium carbonate, lanthanum oxide and aluminum oxide with purity above 99% as starting materials. 12 The flake titanium source and CaCO3, La2O3, Al2O3 powders are reacted according to the chemical reaction equation 2(1-x)Bi4Ti3O 12+6(1-x)CaCO3+3xLa2O3+3xAl2O3=6(1-x)CaTiO3-xLaAlO3+4(1-x)Bi2O3+6(1-x)CO2 in a stoichiometric ratio, wherein x=0.3, and the ratio of the molar amount of the titanium source to the total molar amount of the calcium source, the latitude source and the aluminum source satisfies 1:10 to ensure sufficient reaction, and at the same time, a first shape-adjusting molten salt (the molar ratio of NaCl and KCl is 1:1) with a mass of 2 times the mass of the mixed powder is added to prepare a mixed material. The mixed material is transferred to a sealed alumina crucible and calcined in a high-temperature furnace at 1000℃ for 4 hours to obtain a first calcined powder. The first calcined powder is repeatedly soaked in 30% nitric acid for 12 hours to remove bismuth-based byproducts, unreacted CaCO3, La2O3, Al2O3 powders, and CaO, a decomposition product of CaCO3. The acid-washed powder is repeatedly rinsed with hot deionized water, and then dried, crushed and sieved to obtain composite perovskite 0.7CaTiO3-0.3LaAlO3 (CTLA) ceramic flake template seed crystals.

[0130] ③ The 0.7CaTiO3-0.3LaAlO3 (CTLA) ceramic sheet template seed crystal was transferred to a mold with a diameter of Φ12mm, and pressed on a dry pressing machine at a pressure of 200MPa to obtain a green block. The green block was sintered in a high-temperature furnace at 1450℃ for 4h to obtain a 0.7CaTiO3-0.3LaAlO3 ceramic material.

[0131] Comparative Example 2 (using only ceramic powder)

[0132] A textured 0.7CaTiO3-0.3LaAlO3 ceramic material, the preparation of which comprises the following steps:

[0133] ① Use calcium carbonate (CaCO3), titanium dioxide (TiO2), lanthanum oxide (La2O3) and aluminum oxide (Al2O3) with a purity of more than 99% as starting materials. Place the raw materials in a 120℃ oven for 12 hours for standby use. Add materials according to the molar ratio of the chemical formula 0.7CaTiO3-0.3LaAlO3, transfer the weighed raw materials to a polyurethane ball mill for primary wet grinding, where the material: ball: deionized water mass ratio = 1:3:1.6, and the ball mill speed is 300r / min. After ball milling for 4 hours, transfer the slurry to a 120℃ oven for drying, and then crush and sieve to obtain a mixed powder. Calcine the mixed powder in a high-temperature furnace at 1150℃ for 4 hours to obtain a calcined powder. Transfer the calcined powder to a polyurethane ball mill for secondary wet grinding, where the material: ball: deionized water mass ratio = 1:3:1, and the ball mill speed is 300r / min. After ball milling for 4 hours, 17 wt% of the binder polyvinyl alcohol (PVA) was added to the slurry, and then evenly stirred for 1 hour and spray granulated to obtain 0.7CaTiO3-0.3LaAlO3 (CTLA) ceramic powder.

[0134] ④ The CTLA powder material was transferred to a mold with a diameter of Φ12 mm, and pressed on a dry pressing machine at a pressure of 200 MPa to obtain a green block. The green block was sintered in a high-temperature furnace at 1450°C for 4 hours to obtain 0.7CaTiO3-0.3LaAlO3 ceramic material.

[0135] Furthermore, in order to verify the progress of the embodiments of the present application, the thermal conductivity and relative dielectric constant ε of the above embodiments and comparative examples are r , quality factor Q×F value and resonant frequency temperature coefficient were tested respectively.

[0136] 1. Thermal conductivity test method: According to the method specified in GB 5598, the thermal conductivity of the sample is tested. The test is repeated three times and the mathematical mean is calculated.

[0137] 2. Relative dielectric constant ε r Test method: According to the method specified in GB 7265.2, measure the corresponding ε r ,The test was repeated three times and the mathematical mean was statistically calculated.

[0138] 3. Quality factor Q×F value test method: According to the method specified in GB 7265.2, the corresponding Q×F value is measured. The test is repeated three times and the mathematical mean is calculated.

[0139] 4. Test method for resonant frequency temperature coefficient: According to the method specified in GJB 3018-97, test the resonant frequency temperature coefficient of the sample. The test is repeated three times and the mathematical mean is calculated.

[0140] The test results are shown in Table 1:

[0141] Table 1

[0142]

[0143] It can be seen from the above test results that in the textured (1-z) CaTiO3-zLaAlO3 ceramic material prepared by mixing (1-x) CaTiO3-xLaAlO3 ceramic flake template seed crystals and (1-y) CaTiO3-yLaAlO3 ceramic powder in the embodiment of the present application, the (1-y) CaTiO3-yLaAlO3 ceramic powder grains can be regularly arranged along the specific direction of the (1-x) CaTiO3-xLaAlO3 ceramic flake template seed crystal, and the orientation probability in the direction of the (1-x) CaTiO3-xLaAlO3 ceramic flake template seed crystal is increased and preferential growth is achieved. Heat can be quickly conducted in these preferential orientations of the prepared textured (1-z) CaTiO3-zLaAlO3 ceramic material, thereby achieving improved thermal conductivity. It can be seen from the above test results that the thermal conductivity value of the textured (1-z) CaTiO3-zLaAlO3 ceramic material prepared in the embodiment is 20 to 40 W / m·k. At the same time, the textured (1-z)CaTiO3-zLaAlO3 ceramic material has the characteristics of high thermal conductivity, high dielectric constant, high quality factor and near-zero resonant frequency temperature coefficient.

[0144] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A textured (1-z) CaTiO 3 -zLaAlO 3 Method for preparing ceramic materials, It is characterized in that The following steps are involved: Preparation of (1-x)CaTiO by molten salt method 3 -xLaAlO 3 Ceramic flake template seed crystal, wherein 0<x<1; (1-y)CaTiO prepared by high temperature solid-state synthesis 3 -yLaAlO 3 Ceramic powder, wherein 0<y<1; The (1-x)CaTiO 3 -xLaAlO 3 Ceramic flake template seed crystal and the (1-y)CaTiO 3 -yLaAlO 3 The ceramic powders are mixed and pressed into ceramic green bodies, and then sintered to make the (1-y)CaTiO 3 -yLaAlO 3 The ceramic powder grains are along the (1-x)CaTiO 3 -xLaAlO 3 The flake directions of the ceramic flake template seed crystals are regularly arranged and oriented to grow, resulting in textured (1-z) CaTiO 3 -zLaAlO 3 Ceramic material, wherein 0<z<1; the textured (1-z)CaTiO 3 -zLaAlO 3 The thermal conductivity of ceramic materials is 20 to 40 W / m·k.

2. The textured (1-z) CaTiO according to claim 1 3 -zLaAlO 3 Method for preparing ceramic materials, It is characterized in that Preparation of the (1-x)CaTiO 3 -xLaAlO 3 The steps of ceramic flake template seeding include: The flaky titanium source is prepared by molten salt method; According to (1-x)CaTiO 3 -xLaAlO 3 The flaky titanium source, the first aluminum source, the first lanthanum source, the first calcium source and the first shape-adjusting molten salt are mixed to form a mixed material, and then subjected to a first calcination treatment to obtain a first calcined powder; The first calcined powder is sequentially acid-washed and water-washed to remove impurities to obtain the (1-x)CaTiO 3 -xLaAlO 3 Ceramic flake template seed crystal.

3. The textured (1-z)CaTiO according to claim 2 3 -zLaAlO 3 Method for preparing ceramic materials, It is characterized in that The flake titanium source includes Bi 4 Ti 3 O 12 , prepare the Bi 4 Ti 3 O 12 The steps of the flake titanium source include: 4 Ti 3 O 12 The stoichiometric ratio of the metal elements in the mixture is obtained by mixing bismuth trioxide and titanium dioxide into a mixed material, mixing the mixed material with a second shape-adjusting molten salt, performing a second calcination treatment, washing with water and drying, and obtaining the Bi 4 Ti 3 O 12 Flake titanium source; and / or, the mass ratio of the total mass of the flaky titanium source, the first aluminum source, the first lanthanum source and the first calcium source to the mass of the first shape-adjusting molten salt is 1:(2-2.5); And / or, the conditions of the first calcination treatment include: calcining at a temperature of 1050-1250° C. for 4-6 hours; And / or, the solution used for pickling includes at least one of nitric acid and hydrochloric acid; and / or, the first lanthanum source comprises at least one of lanthanum oxide, lanthanum carbonate, and lanthanum hydroxide; And / or, the first aluminum source includes at least one of aluminum oxide and aluminum hydroxide; And / or, the first calcium source includes at least one of calcium carbonate and calcium hydroxide.

4. The textured (1-z)CaTiO according to claim 3 3 -zLaAlO 3 Method for preparing ceramic materials, It is characterized in that The first shape-adjusting molten salt and the second shape-adjusting molten salt respectively and independently comprise NaCl and KCl in a mass ratio of 1:(0.5-1.5); and / or, the mass ratio of the total mass of the bismuth trioxide and the titanium dioxide to the mass ratio of the second shape-adjusting molten salt is 1:(2-2.5); And / or, the conditions of the second calcination treatment include: calcining at a temperature of 900 to 1100° C. for 4 to 6 hours; And / or, the (1-x)CaTiO 3 -xLaAlO 3 The size of the ceramic flake template seed crystal is 10 to 100 μm.

5. The textured (1-z) CaTiO according to any one of claims 1 to 4 3 -zLaAlO 3 Method for preparing ceramic materials, It is characterized in that Preparation of the (1-y)CaTiO 3 -yLaAlO 3 The steps of ceramic powder include: According to (1-y)CaTiO 3 -yLaAlO 3 A second aluminum source, a second lanthanum source, a second titanium source, and a second calcium source are mixed to obtain a third calcined powder. The third calcined powder is mixed with a binder and then spray granulated to obtain the (1-y)CaTiO 3 -yLaAlO 3 Ceramic powder.

6. The textured (1-z) CaTiO according to claim 5 3 -zLaAlO 3 Method for preparing ceramic materials, It is characterized in that The second lanthanum source includes at least one of lanthanum oxide, lanthanum carbonate, and lanthanum hydroxide; And / or, the second aluminum source includes at least one of aluminum oxide and aluminum hydroxide; And / or, the second titanium source includes at least one of titanium dioxide and titanium hydroxide; And / or, the second calcium source includes at least one of calcium carbonate and calcium hydroxide; And / or, the adhesive includes at least one of polyvinyl alcohol, hydroxypropyl methylcellulose, and polyacrylic acid; And / or, the temperature conditions of the third calcination treatment include: calcining at a temperature of 1050-1250° C. for 4-6 hours; and / or, the mass ratio of the third calcined powder to the binder is 1:(0.15-0.2); And / or, the (1-y)CaTiO 3 -yLaAlO 3 The average particle size of the ceramic powder is 0.5 to 5 μm.

7. The textured (1-z) CaTiO according to any one of claims 1 to 4 or 6. 3 -zLaAlO 3 Method for preparing ceramic materials, It is characterized in that The preparation steps of the ceramic green body include: 3 -xLaAlO 3 Ceramic flake template seed crystal and the (1-y)CaTiO 3 -yLaAlO 3 Mixing ceramic powders, transferring the mixed powders into a mold, and pressing them into the ceramic green body under a pressure of 150 to 250 MPa; And / or, the sintering treatment condition is: sintering at a temperature of 1430-1470° C. for 4-6 hours.

8. A textured (1-z) CaTiO prepared by the method according to any one of claims 1 to 7 3 -zLaAlO 3 Ceramic materials, It is characterized in that The textured (1-z)CaTiO 3 -zLaAlO 3 Ceramic materials include (1-x)CaTiO 3 -xLaAlO 3 Ceramic flake template seed crystal and along the (1-x)CaTiO 3 -xLaAlO 3 (1-y)CaTiO grown by seeding with ceramic flake template 3 -yLaAlO 3 Ceramic powder.

9. A communication device, It is characterized in that The raw material for manufacturing the communication device includes the textured (1-z) CaTiO prepared by the method according to any one of claims 1 to 7. 3 -zLaAlO 3 Ceramic material, or textured (1-z)CaTiO as claimed in claim 8 3 -zLaAlO 3 Ceramic material.